Taḥlīl Manhaj 2013 Min Ḥaiṡ al-Madkhal al-`Ilmī (Scientific) Wa at-Taqyīm al-Aṣīl (Autentic Assessment) Bi Mu`allim al-Lughah al-`Arabiyyah Bi MIN 4 Banda Aceh: MIN 4 Banda Aceh بمعلم اللغة العربية بـــ (Autentik Assessment) والتقييم الأصيل (Scientific) تحليل منهج 2013 من حيث المدخال العلمي - Nurul Magfirah; Hilmi Hilmi (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2021)
The 2013 curriculum is the current curriculum, the 2013 curriculum is the foundation for schools and staff in carrying out school activities from school equipment to teaching activities. Learning based on the 2013 curriculum must reflect scientific learning activities with an authentic evaluation model to produce a perfect level of learning. The author refers to the Learning Implementation Plan (RPP) to see an overview of scientific learning and authentic evaluation models, because there are indications that the Learning Implementation Plan (RPP) does not provide an overview of scientific learning and authentic evaluation models. This study aims to determine teacher implementation of scientific learning and authentic evaluation models in the teaching and learning process and teacher problems in implementing scientific learning and authentic evaluation models. The method in compiling this scientific essay is a descriptive method, where the author describes the problem and makes a draft to provide an interpretation of the teacher's application of scientific learning and authentic evaluation models in Arabic learning. To collect data, the writer uses data observation and interviews, both of which function to collect data and analyze it so that conclusions can be drawn. The results of the research are the application of scientific learning and the authentic evaluation model carried out by the teacher is almost perfect with several shortcomings such as lack of innovation, information, generality, and the elimination of important points. The implementation rate reaches 85% for scientific learning while the authentic evaluation model is only 50% due to the elimination of points that occur in the Learning Implementation Plan (RPP), Meanwhile, the problem with teachers in applying the scientific approach and authentic assessment is the teacher's lack of attention to the scientific approach and authentic assessment, writing lesson plans that are assisted by others without being accompanied by the teacher's response to study the lesson plans that have been written, so that the teacher's knowledge of scientific and authentic assessments is lacking and it can be seen in the less than perfect RPP writing.